2020
DOI: 10.1016/j.jobe.2020.101607
|View full text |Cite
|
Sign up to set email alerts
|

Optimised cold-formed steel beams in modular building applications

Abstract: This is a repository copy of Optimised Cold-Formed Steel Beams in Modular Building Applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 25 publications
(64 reference statements)
0
18
0
Order By: Relevance
“…Besides, GA is an unconstrained optimization algorithm, which means any constraint has to be incorporated directly into the objective function through an augmented Lagrangian approach or penalty factors [49]. Gatheeshgar et al [111] indicated that one of the significant advantages of PSO over GA is that the practical manufacturing and theoretical constraints could be incorporated easily in the case of PSO. Leng et al's study [81] preferred SA more than GA since it ran only on one design instead of a population and led to computational cost savings [112].…”
Section: Optimization Algorithms 231 Stochastic Search Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, GA is an unconstrained optimization algorithm, which means any constraint has to be incorporated directly into the objective function through an augmented Lagrangian approach or penalty factors [49]. Gatheeshgar et al [111] indicated that one of the significant advantages of PSO over GA is that the practical manufacturing and theoretical constraints could be incorporated easily in the case of PSO. Leng et al's study [81] preferred SA more than GA since it ran only on one design instead of a population and led to computational cost savings [112].…”
Section: Optimization Algorithms 231 Stochastic Search Algorithmsmentioning
confidence: 99%
“…A variety of optimization techniques have been used in the earlier research to optimize CFS members, such as graph theory and ant colony optimization [114], Genetic Algorithms (GA) [20,50,98,113,[117][118][119][120][121][122][123][124], Particle Swarm Optimization (PSO) [21,91,111,[125][126][127][128][129][130], Direct Multi Search Optimization (DMS) [115], the Big Bang-Big Crunch algorithm (BB-BC) [131], self-shape optimization method [132], parameter-free method [133], Neutral Dynamic model [23,134,135], Simulated Annealing (SA) [112,113,124,136], the Gradient Descent Optimization (GDO) [113,122], the Trust-Region Method (TRM) [116], and Whale Optimization Algorithm (WOA) [37].…”
Section: Existing Studies In the Literature For Structural Optimizati...mentioning
confidence: 99%
“…The structural performance of these channels, when it is used as a beam, was investigated by Degtyreva et al [25] , [26] , [27] and found that the reduction of the maximum reduction bending capacity is only 23% and 11% for distortional and local buckling failure. Moreover, Gatheeshgar et al [73] introduced these staggered slotted perforations to optimised CFS beams for modular building applications. Therefore, the concept of staggered slotted perforations is proposed to be incorporated into steel-framed modular buildings to limit the heat transfer through panels.…”
Section: Development Of Affordable Modular Unitmentioning
confidence: 99%
“…However, limited research has been carried out in this area [36][37][38][39][40][41][42][43][44]. Satheeskumar et al [45] investigated sustainable benefits of a crosslaminated timber-CFS composite beam, and Gatheeshgar et al [46] studied the role of an optimised CFS beam in modular constructions. A cross-laminated timber-CFS composite beam has enhanced flexural capacity by 20% compared to the individual capacities of both members [45], whereas optimised CFS sections such as Lipped Channel Beam (LCB), folded flange sections and super sigma sections have increased moment capacity by 30%, 60% and 65%, respectively [46].…”
Section: Countrymentioning
confidence: 99%
“…Therefore, both methods set the path to high-rise modular buildings with enhanced lateral stability. Figure 7 illustrates recent high-rise modular structures built all over the world using both methods [46]. Panel-based modules used in the in-filled frame method instead of traditional block or brick walls to eliminate various disadvantages including wastage, issues of being weatherproof and high cost.…”
Section: Overview Of Modular Constructionmentioning
confidence: 99%